PERAN BUDAYA ORGANISASI DALAM MENINGKATKAN RETENSI KARYAWAN - Shierli Wijaya (Jurnal Bina Manajemen, 2022)
The study of organizational culture is interesting because it deals with the uniqueness, the characteristics that distinguish one organization from another. Organizational culture is a system of shared meaning held by members that distinguishes an organization from other organizations. This system of shared meaning is a set of key characteristics that organizations uphold. Organizational culture is created by the "founder" i.e. people who have already been in the organization, where the culture becomes a tradition, an inherent habit, which is embraced by members of the organization. Culture relates to something of positive value, which is unique which is the character of an organization. As well as the pattern of leadership, administrative neatness, discipline, reward system, authority system, and many more cultures adopted by the organization. Therefore, organizational culture should make a positive contribution to organizational development, especially in increasing employee retention in an organization as well as individuals and teams within the organization